Experiences of young Australian mothers with infant feeding - Christa Buckland; Debra Hector; Gregory S. Kolt; Jack Thepsourinthone; Amit Arora (BMC, 2022)
Abstract Background Despite the overwhelming evidence of health and other benefits of breastfeeding and recommendations to breastfeed by peak health bodies, breastfeeding rates are significantly lower than recommended in Australia and globally. Young mothers are identified as being at high risk of not breastfeeding their infants according to infant feeding recommendations. This study aimed to gain an in-depth understanding of young Australian mothers' experiences of infant feeding, and to explore the factors which facilitated or hindered adherence to recommended breastfeeding practices. Methods Purposive and snowball sampling were used to recruit young mothers in Australia (n = 17) aged 18-25 years who had given birth to their first child within the last two years. Data were collected through semi-structured interviews via online videoconferencing. Interviews were audio-recorded, transcribed verbatim, coded, and subsequently analysed. Thematic analysis was conducted using Quirkos, a qualitative data management and analysis software. Results Four major themes were identified: Breastfeeding is challenging; Feeling judged about infant feeding choices; Experiences with breastfeeding support; and Experiences and views on breastfeeding education. Most mothers reported experiencing breastfeeding challenges, particularly those arising from lactation difficulties, yet many were able to overcome these challenges through their determination to breastfeed. Many mothers expressed perceiving judgement from others for breastfeeding in public. Some mothers who were bottle feeding their infants, whether with expressed breast milk or infant formula, felt that they were being judged for using a bottle. Many mothers reported professional, partner, family, and peer support as critical facilitators to the continuation of breastfeeding. Most mothers shared positive experiences of attending breastfeeding education sessions, but indicated the need for community education to reduce judgement toward mothers' infant feeding decisions. Conclusions The barriers and enablers to infant feeding experienced by young mothers are similar to those experienced by mothers of all ages. Young mothers experience significant breastfeeding challenges and need support from partner, family, peers, and professionals to continue breastfeeding in line with recommendations. Breastfeeding campaigns to support young mothers should be aimed at the wider community to increase awareness of breastfeeding challenges, reduce stigma associated with breastfeeding in public, and to support mothers in their infant feeding decisions.